Sistem Pendukung Keputusan Pemilihan Forum Mahasiswa dengan Metode Weighted Product (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2017)
The Selection of forums for students to find a quality forum and can answer their problems that they face about the theme of the lecture is not easy. Generally, students or users face confusion with the many variations of forums on the internet media. In this study, the decision support system designed the selection of student forums in providing the best forum selection solution. The method used in this case study is Weighted Product with the criteria used are the date of posting, the number of answers (answer), the number of people who see (views) and ranking from the Alexa site. Test results from the application are able to select the best alternative for forum selection. In this case, the alternative is the recommendation of the forum that will be recommended to the students based on the weighting of the criteria specified. In general, the results of the four tests wirh verification and validation testing can be concluded that the recommended forum is in accordance with the weighting that is done with the value of accuracy of 100%.